Exponential ADE Solution Based Compact Model of Planar Injection Enhanced IGBT Dedicated to Robust Power Converter Design - Petar Igic (IEEE Transactions on Power Electronics, 2015)
The compact model of an injection enhanced insulatedgate bipolar transistors based on the exponential solutionof the ambipolar diffusion equation is presented in this paper. Tomodel plasma carrier distribution, an exponential shape functionis used, and in steady-state forward bias operation, the plasmacarrier concentration has a distribution of catenary form with justtwo exponential basis functions, while in transient operation, morecomplex profiles can be approximated using a number of exponentialbasis functions with a range of decay length parameters,shorter than the steady state ones. The device model developedhas been implemented in Saber circuit simulator and successfullytested against complete set of high current, high voltage experimentalresults.